The Right to Health: COVID-19 Pandemic and the Opportunity to Transform Mental Health Inequalities in Indonesia - Anindyajati, Gina; Mardiasmo, Diashati Ramadhani; Sekarasih, Laras; Susilaradeya, Damar; Takwin, Bagus; Pelupessy, Dicky C.; Diatri, Hervita (Frontiers in Public Health, 2022)
The COVID-19 pandemic has caused major catastrophes worldwide. Indonesia, a heterogenous, densely populated developing country, with a considerable socio-economic gap, has succumbed to extensive setbacks, particularly in access to mental health services. This paper captured the state of public mental health in Indonesia using data from various national surveys. The increasing occurrence of mental health problems in the general population, healthcare workers and vulnerable populations were highlighted. Despite its high need, the pandemic has caused disruption of mental health services at hospitals and primary-care facilities and limited scope of mental health services in Indonesia. This paper provided practical recommendations for the Indonesian government that focuses on mental health promotion and prevention measures and comprehensive psychosocial support programs that will ensure equal access to mental health services.